Reliability of the Ekblom soccer-specific endurance test - Williams, M. D.; Wiltshire, H. D.; Lorenzen, C.; Wilson, C. J.; Meehan, D. L.; Cicioni Kolsky, D. J. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to explore and quantify measurement reliability of the Ekblom endurance test. Experienced university soccer players (n = 19; age = 20.5 ± 2.5 years; mass = 80.4 ± 9.8 kg; and stature = 179.0 ± 6.0 cm) completed the Ekblom endurance test on 3 separate occasions. Time to complete trial 1 (549 ± 26 seconds) and trial 2 (547 ± 26 seconds) was analyzed, and despite no significant difference (F1,18 = 4.119, p = 0.057, nP^2 = 0.186) between trials, some evidence of systematic bias was observed in the data. Therefore, trial 2 data were compared with those of trial 3 (548 ± 27 seconds), with trial 1 data removed. The subsequent analysis (F1,18 = 0.740, p = 0.401, nP^2 = 0.039) showed a reduction in the risk of making a type II error when compared with the previous analysis. From the reliability analyses (3,1 intraclass correlation = 0.983, SEM = ±3 seconds, smallest worthwhile change = 5 seconds, standard error of prediction [95% confidence intervals] = ± 9 seconds), a high level of measurement reliability was observed and the sensitivity of the test to monitor changes was good. In summary, it was shown that a test that involves a variety of soccer-specific forms of locomotion can be highly reliable and sensitive to detect change. In light of the systematic bias found, we do, however, recommend a familiarization session to be scheduled before the introduction of this test.